Artificial Intelligence and Its Ethical Implications for Marketing - Ana Rita Gonçalves; Diego Costa Pinto; Paulo Rita; Tamara Pires (Ital Publication, 2023)
Despite the recent developments in AI, ethical questions arise when consumers contemplate how their data is being treated. This paper develops a conceptual model building on the theory of acceptance, risk, trust, and attitudes towards AI to understand the drivers that lead consumers to accept AI, considering consumers' ethical concerns. The model was empirically tested with 200 consumers of AI marketing services. The findings reveal that perceived risk significantly impacts attitudes toward AI, ethical concerns, and perceived trust and suggest a significant association between perceived risk, ethical concerns, and social norms. This research provides important theoretical and managerial implications for the ethical aspects of AI in marketing by highlighting the ethical and moral questions surrounding AI's acceptance. Doi: 10.28991/ESJ-2023-07-02-01 Full Text: PDF